Defining the molecular response to ischemia-reperfusion injury and remote ischemic preconditioning in human kidney transplantation - Nordström, Johan; Badia-I-Mompel, Pau; Witasp, Anna; Schwarz, Angelina; Evenepoel, Pieter; Moor, Matthias B.; Wennberg, Lars; Saez-Rodriguez, Julio; Wernerson, Annika; Olauson, Hannes (PloS one, 2024)
Ischemia-reperfusion injury (IRI) inevitably occurs during kidney transplantation and extended ischemia is associated with delayed graft function and poor outcomes. Remote ischemic preconditioning (RIPC) is a simple, noninvasive procedure aimed at reducing IRI and improving graft function. Experimental studies have implicated the kynurenine pathway as a protective mechanism behind RIPC. First, paired biopsies from 11 living kidney donors were analyzed to characterize the acute transcriptomic response to IRI. Second, 16 living kidney donors were subjected to either RIPC (n = 9) or no pretreatment (n = 7) to evaluate the impact of RIPC on the transcriptomic response to IRI. Finally, the effect of RIPC on plasma metabolites was analyzed in 49 healthy subjects. There was a robust immediate response to IRI in the renal transcriptomes of living-donor kidney transplantation, including activation of the mitogen-activated protein kinase (MAPK) and epidermal growth factor receptor (EGFR) pathways. Preconditioning with RIPC did not significantly alter the transcriptomic response to IRI or the concentration of plasma metabolites. The present data validate living-donor kidney transplantation as a suitable model for mechanistic studies of IRI in human kidneys. The failure of RIPC to alter transcriptomic responses or metabolites in the kynurenine pathway raises the question of the robustness of the standard procedure used to induce RIPC, and might explain the mixed results in clinical trials evaluating RIPC as a method to attenuate IRI.